(untitled) (CaJoST, 2024)
The challenges of continual depletion, economic crisis and environmental issues of petroleum fuels have attracted the scientists’ interest to seek alternatives to fossil fuels. Biodiesel is the alternative to petrol diesel because; it has similar physicochemical properties to petrol diesel. However, biodiesel has not been competing favourably well economically with petrol diesel due to the high cost of production. In this work, biodiesel was produced from luffa cylindrica seed oil using native, nano and modified nano kaolinite clay as a heterogeneous catalyst. Kaolinite clay sourced from Kankara town in Katsina State was purified, calcined and impregnated to produce the catalyst. Oil extraction from Luffa cylindrica) was carried out using a solvent extraction method using hexane at 60 oC for 1 hour. The physicochemical parameter of the oil was determined, which include; percentage yield (24.956 %), Acid Value (6.316 mgKOHg-1), Refractive Index (1.46 %), Saponification Value (184.62 mg.g-1), Density (0.822 gcm-3), Iodine Value (63.28 g.100-1), FFA (9.433mg.KOHhg-1), and Specific Gravity (0.937Kg/cm3), viscosity (6.22), peroxide value (3.78), and ester value (188.79) respectively. CuO/kaolin was used for the conversion of luffa cylindrica oil into biodiesel and it was seen as a source for biodiesel production since the fuel properties of biodiesel produced using the catalyst were found to fulfil the majority of the ASTM (American Society for Testing and Materials standards) for biodiesel. The oil also can be used in soap, shoe polish and cosmetics manufacturing. It can also be seen that Modification of the catalysts used also leads to a faster conversion, in general, it can be seen that kaolin is a promising catalyst for the heterogenous transesterification of Luffa cylindrica seed oil.